Ginsenoside Rb1 attenuates neuroflammation via activating Wnt/β-catenin signaling pathway to exert neuroprotective effect on cerebral ischemic-reperfusion injury - Liu, Ruo-jing; Zhao, Xue; Zhu, Yi-zhen; Fu, Ling-Ling; Ge, Guo; Zhu, Jun-de (Frontiers in Aging Neuroscience, 2025)
PurposeTo explore the molecular mechanism of G-Rb1 regulating microglia polarization through Wnt/β-catenin signaling pathway to alleviate cerebral ischemia-reperfusion injury in mice.MethodsC57BL/6J mouse middle cerebral artery occlusion/reperfusion (MCAO/R) model and microglia (BV2) oxygen-glucose deprivation/reoxygenation (ODG/R) model were used. The neuroprotective effect of G-Rb1 in vivo and in vitro was evaluated by measuring nerve function deficit, cerebral blood perfusion recovery, infarct volume and cell viability. Immunofluorescence, flow cytometry, Western blot and qRT-PCR were used to evaluate the effects of G-Rb1 on the Wnt/β-catenin signaling pathway and microglia phenotypic polarization mediated neuroinflammation in vivo and in vitro.ResultsCompared with the Sham group, the symptoms of neurological impairment, cerebral blood perfusion, cerebral infarction volume and inflammatory reaction were increased in the IRI group. Compared with the IRI group, G-Rb1 group showed less symptoms of neurological impairment, increased cerebral blood perfusion, decreased cerebral infarction volume, increased proportion of M2-type microglia, increased release of anti-inflammatory factors, reduced inflammatory response, and up-regulated β-catenin expression while down-regulated GSK-3β expression. It was demonstrated that G-Rb1 activates the Wnt/β-catenin signaling pathway after CIRI. Compared with G-Rb1 group, G-Rb1 + XAV939 group had more neurological impairment, increased cerebral infarction volume, increased M1 microglia proportion, and increased neuroinflammation. Meanwhile, β-catenin expression decreased while GSK-3β expression increased. The results of in vitro experiments were similar to those of in vivo, which demonstrated that G-Rb1 may alter microglial polarization phenotype through Wnt/β-catenin signaling pathway and alleviate neuroinflammatory response after CIRI.